Examining Entrepreneurship Significant Factors affecting the Performance of MSE’s in Ethiopia, Horn of Africa - Adula , Metasebia; Kant, Shashi (International Journal of Law Policy and Governance, 2022)
This research article has examined the Influence of Entrepreneurship Determinants on MSE’s Performance in Ethiopia. SME entrepreneurs working in West Guji Zone Bule Hora town, Ethiopia used as sample area for data collection. Purposive and stratified sampling was employed to select the respondents. Using a pre-tested survey questionnaire a total of 208 entrepreneurs’ as respondents was retained. Correlation analysis and Spearman's rho regression was used for hypothetical testing. The research enclosed entrepreneurship as determinant on MSE’s Performance. Through evocative statics it is manifested that motivation and self-drive, tolerance to work hard, creativity, flexibility and adaptability to new ideas were the main determinants that affects the performance of MSE’s in the studied area. Inferential statics signified that, there is statistically significant contextual relation between exploratory variables on explained variables. This research has shifted the application of entrepreneurship determinants from developed countries to an emerging like Ethiopia. The research also provide some perceptive implications for business managers and researchers.